Bisphosphonates and osteonecrosis of jaws - Geetha Vijay; Vijay Raghavan (Wolters Kluwer Medknow Publications, 2012)
Bisphosphonates are used to treat osteoporosis. Paget disease of bone and other metabolic bone diseases, multiple myeloma, and skeletal events associated with metastatic neoplasms- In 2003, the first reports describing osteonecrosis of the jaw (ONJ) in patients receiving bisphosphonates were published. About 95% of these cases occurred among cancer patients receiving high-dose intravenous bisphosphonates. Approximately 5% of the reported cases have been in osteoporosis patients receiving low dose bisphosphonate therapy. The mandible is more commonly affected than the maxilla (2:1 ratio), and 60% of cases are preceded by a dental surgical procedure. Oversuppression of bone turnover is probably the primary mechanism for the development of this condition, although there may be contributing comorbid factors. All sites of potential jaw infection should be eliminated before bisphosphonates therapy is initiated in these patients to reduce the necessity of subsequent dentoalveolar surgery. Conservative debridement of necrotic bone, pain control, infection management, use of antimicrobial oral rinses, and withdrawal of bisphosphonates are preferable to aggressive surgical measures for treating this condition. The purpose of the present article is to enlighten the dental fraternity about this frequently prescribed class of drugs with regard to its types and mode of action, and the implication of bisphosphonates-induced ONJ.